Scottish Portias: Women in the Courts in Mediaeval Scottish Towns - Ewan, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1992)
AbstractBy studying the fifteenth and early sixteenth-century records of several Scottish towns, this paper examines the roles of women in the town courts of mediaeval Scotland. It argues that, although women faced certain legal disadvantages, they were able to make use of the courts to advance their own interests. An examination of the actions of these women shows that the legal restrictions were often flouted in practice, with women arguing their own cases and even occasionally acting as procurators for others. This case study points out the necessity of examining the practical application of the law as well as legal codes and treatises before reaching conclusions about women s status. By showing the active part which women took in the legal life of the town, it also suggests that Scottish urban history needs to take into account women's experiences in reconstructing the life of mediaeval towns.